2015
DOI: 10.1007/s12094-015-1350-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of plasma fibrinogen and D-dimer in predicting the chemotherapy efficacy and prognosis for small cell lung cancer patients

Abstract: Fibrinogen and D-dimer levels after two cycles of chemotherapy are predictors for response on chemotherapy and prognosis in SCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 34 publications
5
58
2
Order By: Relevance
“…These findings are in accordance with previous reports regarding other malignancies, such as lung, [35] esophageal, [36] gastric, [37] colorectal, [34] and ovarian [7] cancer. Most importantly, high plasma fibrinogen levels have been correlated with poor response to therapy, including response to trastuzumab treatment in HER2-positive breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with previous reports regarding other malignancies, such as lung, [35] esophageal, [36] gastric, [37] colorectal, [34] and ovarian [7] cancer. Most importantly, high plasma fibrinogen levels have been correlated with poor response to therapy, including response to trastuzumab treatment in HER2-positive breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, D‐dimer levels can be utilized as a predictor of immediate mortality in patients with in‐hospital cardiac arrest . An increasing body of evidence suggests the existence of a relationship between activation of coagulation and tumor angiogenesis, progression, and metastatic spread . Fibrinogen and D‐dimer levels are easily obtainable tests commonly ordered for inpatients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that plasma fibrinogen and/or D‐dimer levels can predict poor prognosis in several types of malignancies including ovarian, breast, colorectal, lung, gastric, and pancreatic cancer . In lung cancer, plasma fibrinogen and D‐dimer levels have been shown to be associated with tumor pathological stage, response to therapy, and survival . In epithelial cell origin ovarian cancer, pretreatment plasma D‐dimer and fibrinogen have been shown to be able to predict disease progression and surgical outcome as well as to help identify and treat high‐risk populations .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that plasma fibrinogen level is upregulated in various cancers and may account for progression and metastasis [58]. However, there are conflicting findings on the role of plasma fibrinogen and survival outcomes in RCC.…”
Section: Introductionmentioning
confidence: 99%